Leptin in sperm analysis can be a new indicator - Önel, Tuğçe; Ayla, Şule; Keskin, İlknur; Parlayan, Cüneyd; Yiğitbaşı, Türkan; Kolbaşı, Bircan; Varlı Yelke, Tuba; Şenel Ustabaş, Tuğba (Elsevier GMBH, 2019)
Purpose Radiotherapy, chemotherapy, various tumors and invasive surgery can result in ejaculatory dysfunction and testicular insufficiency. Sperm cryopreservation is the only method which can provide a baby for couples. Cryopreservation freezes tissues and cells, allowing them to be stored for future use by stopping all biological activities. Cryopreservation can cause some harmful changes in the structure and function of the sperm. Leptin molecule plays many roles in most biological processes including the satiety and cell renewal, proliferation, angiogenesis, modulation of energy expenditure and regulation of the neuroendocrine system. Leptin was also reported to be associated with spermatogenesis in several studies. Methods This study aims to use leptin molecule as a parameter for sperm motility and DNA fragmentation before and after the cryopreservation. In this study, semen samples were taken from 30 normospermic male volunteers. Each semen sample was examined for the same parameters before and after the cryopreservation. Samples were analyzed before and after cryopreservation in terms of sperm motility by morphological sperm analysis with spermac stain dye, DNA fragmentation by TUNEL assay, ultrastructural analysis with transmission electron microscopy (TEM), seminal leptin levels by ELISA method and reactive oxygen species (ROS) levels by colorimetric method. Results Decreased sperm motility, distribution of sperm morphology and increased DNA fragmentation were determined after cryopreservation. Similarly, seminal ROS and leptin levels were also increased significantly. There was a negative correlation between seminal leptin and sperm motility. Additionally, there was a positive correlation between seminal leptin and DNA fragmentation. Conclusion According to these results, leptin molecule can be used as a marker for sperm motility and DNA fragmentation before and after cryopreservation. We think that the results of this study can contribute to further studies in the clinical aspect.
WOS: 000461000600006
PubMed ID: 30482507
Keywords: Cryopreservation; DNA Fragmentation; Leptin; Motility; Sperm